2015
DOI: 10.1002/eqe.2681
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship of seismic intensity measures and the accumulation of damage on concrete gravity dams using incremental dynamic analysis

Abstract: Summary Nonlinear analysis tools are gaining prominence for the design and evaluation of concrete gravity dams. The performance limits of concrete gravity dams within the framework of performance based design are challenging to determine in comparison to those used for the assessments based on linear elastic analyses. The uncertainty in quantifying the behavior of these systems and the strong dependence of the behavior on the ground motion play an important role. The purpose of the study is to quantify the dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Routine scalable parameters of ground motion, which can be selected as IM, include Peak Ground Acceleration (PGA), peak ground velocity, spectral acceleration, spectral velocity, Arias Intensity, speci c energy density, and maximum incremental velocity [16,38]. It should be indicated that the rst four items are frequently applied to seismic evaluation of dams through IDA [12,13,38,39]. Choosing S a (5%; T 1 ) as IM, by Alembagheri and Ghaemian, has made a lower coe cient of variation in all ranges of DMs in IDA curves [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine scalable parameters of ground motion, which can be selected as IM, include Peak Ground Acceleration (PGA), peak ground velocity, spectral acceleration, spectral velocity, Arias Intensity, speci c energy density, and maximum incremental velocity [16,38]. It should be indicated that the rst four items are frequently applied to seismic evaluation of dams through IDA [12,13,38,39]. Choosing S a (5%; T 1 ) as IM, by Alembagheri and Ghaemian, has made a lower coe cient of variation in all ranges of DMs in IDA curves [12].…”
Section: Resultsmentioning
confidence: 99%
“…Choosing S a (5%; T 1 ) as IM, by Alembagheri and Ghaemian, has made a lower coe cient of variation in all ranges of DMs in IDA curves [12]. In another research performed by Soysal et al, it was revealed that PGA and spectral velocity at the rst mode (S v (5%; T 1 )) played a signi cant role compared to the other IMs in the prediction of cumulative damage states [39]. Since the purpose of this study is the assessment of cumulative damage states, PGA is selected as the main IM parameter.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the RTR variability in the IDA capacity functions, they should be summarized using some central values like the mean, median, and 16% and 84% fractiles. [47], (c) gravity dam [48], (d) gravity dam [49], (e) gravity dam [43], (f) arch dam [50], (g) gravity dam [51], and (h) gravity dam [52]. PGA, peak ground acceleration.…”
Section: Incremental Dynamic Analysismentioning
confidence: 99%
“…Secant unloading was applied in cyclic loading. The description and the validation of the finite element model was previously presented by Soysal et al [22] in detail.…”
Section: Olm Versus Finite Elment Simulationsmentioning
confidence: 99%